2005
DOI: 10.1108/09590550510581485
|View full text |Cite
|
Sign up to set email alerts
|

Customer perceptions of e‐service quality in online shopping

Abstract: Purpose -This paper develops a research model to examine the relationship among e-service quality dimensions and overall service quality, customer satisfaction and purchase intentions. Design/methodology/approach -Data from a survey of 297 online consumers were used to test the research model. Confirmatory factor analysis was conducted to examine the reliability and validity of the measurement model, and the structural equation modelling technique was used to test the research model. Findings -The analytical r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

48
660
6
65

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 985 publications
(878 citation statements)
references
References 42 publications
48
660
6
65
Order By: Relevance
“…Similarly, performance, features, structure, aesthetics, reliability, serviceability, security and system integrity, trust, responsiveness, service differentiation and customization, web store police, reputation, assurance and empathy were the range of elements offered by Madu and Madu (2002) for assessing web site design. Thus there are a variety of e-service quality dimensions that may have a significant impact on online users' perceptions of quality (Lee and Lin 2005;Alanezi et al 2010). …”
Section: E-service Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, performance, features, structure, aesthetics, reliability, serviceability, security and system integrity, trust, responsiveness, service differentiation and customization, web store police, reputation, assurance and empathy were the range of elements offered by Madu and Madu (2002) for assessing web site design. Thus there are a variety of e-service quality dimensions that may have a significant impact on online users' perceptions of quality (Lee and Lin 2005;Alanezi et al 2010). …”
Section: E-service Qualitymentioning
confidence: 99%
“…The concept of e-service quality is derived from that of quality of traditional services, and eservice quality can be the key important factor for online organizations with many online organizations failing due to inadequacy in that regard (Vidgen and Barnes 2002;Kim et al 2009). Collier and Bienstock (2006) conceptualized e-service quality as users' perceptions of the outcome of the service delivery and included service recovery perceptions in the event of service failure; e-service quality is recognized as a significant online factor (Santos 2003;Lee and Lin 2005;Li and Suomi 2009). Quality e-services can provide competitive advantage online by improving organizational performance and clients' satisfaction (Santos 2003).…”
Section: E-service Qualitymentioning
confidence: 99%
“…Not enough is known regarding how customers perceive and evaluate electronically delivered services. Lee and Lin [10] have also recently highlighted the need for further research to measure the influence of e-service on customer-perceived service quality and satisfaction [1]. This study considers the five factors perceived usefulness, perceived ease of use, subjective norm, consumer awareness about mobile banking and perceived risks associated with mobile banking.…”
Section: Introductionmentioning
confidence: 99%
“…Customer satisfaction and customer retention are increasingly developing into key success factors in e-banking [2]. Technology, in particular, has been increasingly employed in service organizations to enhance customer service quality and delivery, reduce costs, and standardize core service offerings [1], [9][10][11]. Mobile banking service allows customers to manage their accounts with ease.…”
Section: Introductionmentioning
confidence: 99%
“…As regards the effects of consumers' perception of online retailers' ethical behaviour on consumer purchase and revisit intentions it was found that perceived ethics of an Internet retailer's website significantly affected consumers' trust and attitudes to the retailer's website that eventually had positive impacts on purchase and revisit intentions (Limbu et al, 2012). Furthermore, to enhance customer purchase intentions, online stores should develop marketing strategies to better address the trustworthiness, reliability, and responsiveness of web-based services (Lee & Lin, 2005).…”
Section: Literature Reviewmentioning
confidence: 99%